Characterization of urosepsis in a tertiary hospital: 5-year retrospective study on prevalence and risk factors in Palestine - Bsharat, Ibrahim; Sadaqa, Dana; Shoeibat, Ayman; Rjoub, Hammam; Yaish, Mohammad; Arafat, Hasan; Hindiyeh, Musa; Sabateen, Ali (The Journal of Infection in Developing Countries, 2025)
Introduction: The objective of this study was to characterize the occurrence of urosepsis in oncology patients and to explore the potential factors influencing its development and outcomes. Urosepsis is a serious systemic infection originating from a urinary tract infection. Its management is particularly challenging in immunocompromised oncology patients. Methodology: A retrospective review of 337 oncology patients diagnosed with urosepsis between 2019 and 2023 was conducted. Various clinical and demographic factors were examined, including patient gender, type of tumor (solid or liquid), nephrostomy, presence of a double J (DJ) stent, diabetes mellitus, length of hospital stay, and use of central lines. Statistical analysis was performed to assess associations between these variables and urosepsis. Results: Males were found to be at higher risk to develop urosepsis (p: 0.039). Escherichia coli was the most commonly identified pathogen. However, none of the analyzed factors, including tumor type (p: 0.432), nephrostomy (p: 0.503), DJ stent (p: 0.325), diabetes mellitus (p: 0.637), length of hospital stay (p: 0.185), or presence of a central line (p: 0.122), showed a statistically significant association with the occurrence of urosepsis. Conclusions: This study is the first to examine urosepsis in oncology patients in Palestine. The findings highlight the increased risk for developing urosepsis in male gender; however, the other factors studied were not significant. The results cannot be generalized to all hospitalized patients as the studied population was in a tertiary hospital, and a bigger sample size is recommended for future studies to allow generalizability of the results.